Emotional Engineering, Vol.5 - Fukuda, Shuichi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a review of the latest research on emotion in engineering, with a particular focus on design and manufacturing. Topics include experience, happiness, cognitive science, neuroscience, additive manufacturing, universal design, branding, teamwork. Throughout the book, the emotions of the end users of engineering products are discussed, as well as the perspective of the expert. The book provides researchers, students, and practicing engineers with an opportunity to examine research and practice in engineering from a different perspective, and offers pointers to how to collaborate with people from other fields to help achieve a more connected society. .
Chapter 1 Shuichi Fukuda, "From Product to Experience" -- Chapter 2 Shuichi Fukuda, "Grayscale: Its Emotional Significance" -- Chapter 3 Shuichi Fukuda,"Context-driven Engineering" -- Chapter 4 Takashi Maeno, "Four Factors of Happiness (Well-Being) Should be the Design Parameters of Service/Products" -- Chapter 5 Kazuhiro Ueda, "Cognitive Mechanism for Selecting New Products:A Cognitive Neuroscience Perspective" -- Chapter 6 Yoshiaki Kikuchi, "The Nostalgic Brain: Its Neural Basis and Positive Emotional Role in Resilience" -- Chapter 7 Anne-Lise Rias,Carole Bouchard, "Design for Additive Manufacturing: A Creative Approach" -- Chapter 8 Susan Kett, Sandro Wartzack, "Universal Design-An Old Fashioned Paradigm?" -- Chapter 9 Susan Kett, Sandro Wartzack, "Considering Users' Emotions in Product Development Processes and the Need to Design for Attitudes" -- Chapter 10 Philip Farrugia, "Branding in Automotive Design" -- Chapter 11 Itsaso Gonzalez, "Brand Experience" -- Chapter 12 Gillian Hatcher, "Humor Processes for Creative Engineering Design" -- Chapter 13Aysar Ghassam, "Food for Thought: Using The RECIPE Initiative to Increase Students' Motivation in Vehicle Design Group Work".-Chapter 14 Josip Stjepandic, Josip Burusic, "Emotional Experience by Functional Digital Mock-up" -- Chapter 15Lee Suehye, Seiko Shirasaka, "Tangible Learning: How to Enhance.
Keywords: Engineering design; Industrial Management; Customer relations -- Management; Manufactures; Emotions; Cognitive psychology; Engineering Design; Industrial Management; Customer Relationship Management; Machines, Tools, Processes; Emotion; Cognitive Psychology